The preponderance of nonsynonymous A-to-I RNA editing in coleoids is nonadaptive - Jiang, Daohan; Zhang, Jianzhi (Nature communications, 2019)
A-to-I editing enzymatically converts the base adenosine (A) in RNA molecules to inosine (I), which is recognized as guanine (G) in translation. Exceptionally abundant A-to-I editing was recently discovered in the neural tissues of coleoids (octopuses, squids, and cuttlefishes), with a greater fraction of nonsynonymous sites than synonymous sites subject to high levels of editing. Although this phenomenon is thought to indicate widespread adaptive editing, its potential advantage is unknown. Here we propose an alternative, nonadaptive explanation. Specifically, increasing the cellular editing activity permits some otherwise harmful G-to-A nonsynonymous substitutions, because the As are edited to Is at sufficiently high levels. These high editing levels are constrained upon substitutions, resulting in the predominance of nonsynonymous editing at highly edited sites. Our evidence for this explanation suggests that the prevalent nonsynonymous editing in coleoids is generally nonadaptive, as in species with much lower editing activities. The neural tissues of coleoids have a greater fraction of nonsynonymous sites than synonymous sites subject to high levels of A-to-I RNA editing, a pattern thought to indicate widespread adaptive editing. Here the authors propose and provide evidence for an alternative, nonadaptive explanation.